THE INFLUENCE OF RETURN ON ASSETS, DEBT TO EQUITY RATIO, AND CURRENT RATIO ON STOCK PRICES WITH PRICE EARNING RATIO AS A MODERATION VARIABLE (Case Study of Food and Beverage Companies Listed on the Indonesian Stock Exchange 2018-2022) - Retnodamayanti, Silvia; Rinofah, Risal; Sari, Pristin Prima (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to test and understand the influence of return on assets, debt to equity ratio, and current ratio on stock prices with price earnings ratio as a moderating variable. The population in this research is all food and beverage companies listed on the Indonesia Stock Exchange in 2018-2022, namely 84 companies. The sampling technique used uses a purposive sampling method, namely a sampling technique that is carried out based on certain considerations. The data analysis method in this research is multiple regression analysis and Moderated Regression Analysis (MRA) using SPSS version 26 software. Based on the results of the hypothesis test, it is concluded that return on assets has a significant positive effect on stock prices, the debt to equity ratio has a negative but not significant effect on stock prices, the current ratio has a positive effect. but not significant to stock prices. The results of the price earnings ratio moderation test were able to moderate the influence of return on assets on stock prices, while the price earnings ratio was not able to moderate the influence of debt to equity ratio, current ratio on share prices.